TIPOLOGI BUDAYA ORGANISASI LEMBAGA PENDIDIKAN PESANTREN: KARAKTERISTIK DAN TRANSFORMASI - Yudik Al Farisi; Ratnawati Ratnawati (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
This study aims to determine the typology of the organizational culture of Islamic boarding schools. This research uses a qualitative case study approach. Data collection techniques using observation, in-depth interviews. While the stages of data analysis techniques used include data collection, data reduction, data presentation, and conclusion of research results. The results obtained are the typology of organizational culture at the Nurul Jadid Islamic Boarding School based on coordination through the bureaus in it. The characteristics and transformations that exist are that Islamic boarding schools are based on furudul 'ainiyah in their organizational culture. While the existing transformation is the transformation of values ??that are integrated into the life of the Nurul Jadid Islamic Boarding School such as religious, independent, togetherness and social care.